2017
DOI: 10.3384/cu.2000.1525.1792163
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Gendered Streams

Abstract: One of the most prominent features of digital music services is the provision of personalized music recommendations that come about through the profiling of users and audiences. Based on a range of "bot experiments, " this article investigates if, and how, gendered patterns in music recommendations are provided by the streaming service Spotify. While our experiments did not give any strong indications that Spotify assigns different taste profiles to male and female users, the study showed that male artists wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…Besides entry values such as where I live and my gender, what friends I had (Spotify was connected to Facebook in 2012), Spotify already had data about my listening habits. Research with bots (Eriksson & Johansson, 2017) has shown that Spotify recommendations tend to take on a gendered pattern for the listener independent of the given gender of the account holder but that genre listening shapes recommendations. Spotify is personalized and the organization of recommendations and relations between artists are based on accumulated choices of other users, thus, trying to find a "true" Spotify structure is impossible.…”
Section: Methodsmentioning
confidence: 99%
“…Besides entry values such as where I live and my gender, what friends I had (Spotify was connected to Facebook in 2012), Spotify already had data about my listening habits. Research with bots (Eriksson & Johansson, 2017) has shown that Spotify recommendations tend to take on a gendered pattern for the listener independent of the given gender of the account holder but that genre listening shapes recommendations. Spotify is personalized and the organization of recommendations and relations between artists are based on accumulated choices of other users, thus, trying to find a "true" Spotify structure is impossible.…”
Section: Methodsmentioning
confidence: 99%
“…They discovered that ideas about activities, values, expertise and technology, in relation to sexuality as well as family influences, are structured by gender norms. In addition, Eriksson and Johansson (2017) found that female artists appear in search results in lower numbers than male artists, independent of searching strategy. They used a range of 'bot experiments' and found out that listening recommendations favoured male artists to a very high extent, which the researchers connect to preservation of masculine norms within the music industry.…”
Section: Connecting Studiesmentioning
confidence: 96%
“…Exempelvis har medierade fankulturers genusmönster inom hårdrock beforskats (Hill, 2016), användningen av medieteknik i musikutbildning (Armstrong, 2011) har studerats ur genusperspektiv, samt liveframträdandens påverkan på rapporteringen om kvinnoidentifierade artister i traditionella medier och sociala medier har jämförts (Danielsen, Kjus & Kraugerud, 2018). I fallet Spotify har de algoritmiska rekommendationernas genusmönster undersökts kvantitativt (Eriksson & Johansson, 2017) och kvalitativt (Werner, 2020).…”
Section: Populärmusik Och Genusunclassified
“…Det framställs inte i marknadsföringsvideorna hur The Equaliser förhåller sig till innehållet i Spotifys katalog och till artisternas genre och popularitet när spellistor skapas. Att Spotifys algoritmiska rekommendationer föreslår en hög andel mansidentifierade artister har visats i forskning (Eriksson & Johansson, 2017). I marknadsföringen diskuteras inte hur Spotifys vanliga algoritmer har en roll i vilka artister och låtar som strömmas.…”
Section: Uteslutningar Och Tystnaderunclassified